3D printing of mechanically robust MXene-encapsulated polyurethane elastomer. (December 2022) - Li, Yuewei; Peng, Shuqiang; Kankala, Ranjith Kumar; Wu, Lixin; Chen, Ai-Zheng; Wang, Shi-Bin
Graphical abstract: Highlights: Elastomers functionalized with modified MXene are subjected to DLP 3D printing. The mechanical properties of the elastomers are enhanced remarkably. The printed 3D objects displayed cyclability and durability. The nanocomposites could be used for advanced stretchable sensors. Abstract: Despite the advantages and success in many fields, most elastomers currently fail to meet specific application requirements owing to their poor mechanical properties and limitations in the manufacturing of complex structures. 3D printing has emerged as an attractive manufacturing process for building a variety of complex structures for custom-configured elastic devices. In this study, we demonstrate the fabrication of elastic nanocomposites based on encapsulating 3-(trimethoxysilyl)propyl methacrylate-modified MXene nanosheets in a photocurable polyurethane acrylate resin (PAR) matrix by digital light processing 3D printing. The mechanical properties of the elastomers are tuned by varying the MXene amount in the PAR. The prepared MXene-PAR nanocomposites containing 0.1% w/w fillers exhibit a tensile strength and elongation at a break of 23.3 MPa and 404.3%, corresponding to an increase of 100.8% and 37.8%, respectively, as compared to the control. Piezoresistive sensors and wearable finger guard sensors are fabricated by coating a MXene-based hydrogel on the surface of the 3D-printed structural parts to determine the printability, mechanical properties, and conductivity. Furthermore, the as-prepared stretchable sensors exhibit long-term working stability. Together, our findings provide a new paradigm for the overall design of 3D-printed elastomers with excellent mechanical properties, which are anticipated to expand the scope of 3D printing.